Parental Burnout and the COVID‐19 Pandemic: How Portuguese Parents Experienced Lockdown Measures. Issue 4 (15th June 2021) - Aguiar, Joyce; Matias, Marisa; Braz, Ana Carolina; César, Filipa; Coimbra, Susana; Gaspar, Maria Filomena; Fontaine, Anne Marie
Abstract : Objective: This work aimed to analyze parental burnout (PB) and establish a comparison between the times before (Wave 1) and during (Wave 2) the COVID‐19 pandemic. Background: The COVID‐19 pandemic brought additional stress to families. The pandemic could be particularly difficult for parents experiencing parental burnout, a condition that involves four dimensions: an overwhelming sense of exhaustion, emotional distancing from the child, saturation or a loss of fulfillment with the parental role, and a sharp contrast between how parents used to be and how they see themselves now. Method: A quasi‐longitudinal research design was adopted, comparing two cross‐sectional studies among Portuguese parents ( N = 995), with an interval of 2 years between each wave of data collection. Participants were surveyed voluntarily through an online questionnaire located on the institutional web platform of the universities involved in the study. Multivariate analysis of covariance was used to take into account the associations among variables, alongside controlling the possible confounding effects. Results: Parents have overall higher parental burnout scores in Wave 2 than Wave 1, with increased exhaustion, emotional distancing, and contrast, but decreased saturation. Although parental burnout levels remain higher for mothers across the two Waves, the growth is greater for fathers than for mothers. Conclusion: Reconciling childcare with paid work is a stressful and new experience for many fathers. However, results suggest that even amid a crisis, some parents had the opportunity to deeply bond with their children. Implications: We expect this work to encourage stakeholders to consider proper intervention strategies to address potential parental burnout. Also, initiatives that strengthen gender equity within parenting context are needed.